2005
DOI: 10.1021/bm049226a
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Characterization of a Four-α-Helix Bundle Protein That Binds the Volatile General Anesthetic Halothane

Abstract: The structural features of volatile anesthetic binding sites on proteins are being investigated with the use of a defined model system consisting of a four-alpha-helix bundle scaffold with a hydrophobic core. The current study describes the bacterial expression, purification, and initial characterization of the four-alpha-helix bundle (Aalpha(2)-L1M/L38M)(2). The alpha-helical content and stability of the expressed protein are comparable to that of the chemically synthesized four-alpha-helix bundle (Aalpha(2)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…Fast and slow components of quenching occur as an anesthetic shifts the conformational equilibrium towards the higher affinity states because the W15 quantum yield in these states is lower. Consistent with this model, the K d for halothane determined from the immediate component of quenching is six-fold higher than that reported at equilibrium (0.68 ± 0.08 mM vs. 0.12 ± 0.02 mM, respectively) (23). Application of this model to interpret the actions of anesthetics on Cys-loop LGICs leads to the prediction that anesthetics bind with higher affinity to the open channel state as compared to the closed channel state.…”
Section: Discussionsupporting
confidence: 63%
“…Fast and slow components of quenching occur as an anesthetic shifts the conformational equilibrium towards the higher affinity states because the W15 quantum yield in these states is lower. Consistent with this model, the K d for halothane determined from the immediate component of quenching is six-fold higher than that reported at equilibrium (0.68 ± 0.08 mM vs. 0.12 ± 0.02 mM, respectively) (23). Application of this model to interpret the actions of anesthetics on Cys-loop LGICs leads to the prediction that anesthetics bind with higher affinity to the open channel state as compared to the closed channel state.…”
Section: Discussionsupporting
confidence: 63%
“…It has been shown that bound volatile general anesthetics alter both local protein dynamics and global protein stability [65][66][67][68]. Both Ab40 and Ab42 peptides have two a-helices (a-helix-I (residues 15-23), a-helix-II (residues 32-36)) connected by a more flexible kink region.…”
Section: Discussionmentioning
confidence: 99%
“…Such sites can be engineered into pre-existing natural protein scaffolds, [1][2][3][4][5] or into proteins designed de novo. [6][7][8][9][10][11][12][13][14] In general, two approaches are used to produce novel binding proteins: (i) In some cases, researchers use principles of rational design to engineer hydrophobic packing and buried polar interactions in the core of a protein to facilitate binding of a small molecule. [6][7][8]15 (ii) Alternatively, high throughput methods, such as phage display or mRNA display, can be used to find rare binding proteins amidst large combinatorial libraries of nonbinding sequences.…”
Section: Introductionmentioning
confidence: 99%